Secular Routes and Theological Drifts in Modern Anthropology - Furani, Khaled (Religion and society, 2018)
Anthropologists have recently shown an increasing concern with secular formations. This exploratory article inquires into the secular formation of anthropology itself by initiating an examination of its relation to theology, deemed anthropology's disciplinary Other. I argue for recognizing a complex relation, whereby anthropology in some ways forgets theology, in others sustains it, and in still others invites critique by it. Analyzing anthropology from its theological edges may reinvigorate awareness of its ethical dimensions as a secular enterprise, as well as help measure its distance from (or proximity to) dominant projects, such as the Enlightenment and the nation-state, which were crucial for its founding in the modern world. An anthropology critically curious about its inherited alienation from theological modes of reasoning may not only become better at investigating the possibilities that cultural forms can take, but also become aware of new forms that the discipline could itself take.